Erosive Osteoarthritis: Presentation of a Treatment-Resistant Case - Ulusoy, Hasan; Akgol, Gurkan; Acet, Gunseli Karaca; Kaya, Arzu; Kamanli, Ayhan (Turkish League Against Rheumatism, 2011)
Erosive osteoarthritis (EOA) is a progressive disease affecting the interphalangeal joints of the hand. It is also known as an inflammatory form of osteoarthritis. Pain, swelling, redness, warmth and limited function of the hand joints are commonly found in most patients with or without Heberden and Bouchard's nodes. Conventional radiographs of the hands show a combination of bony proliferation and erosions, which give characteristic patterns of the affected joints, known as gull-wing and saw-tooth deformities. Since there are no distinguishing laboratory findings between EOA and other common erosive interphalangeal arthropathies, radiographic features still have diagnostic value along with clinical presentation. Thus, recognition of the radiological manifestations may lessen the likelihood of misdiagnoses. A treatment-resistant case of EOA with marked and confusing inflammation is described in this report.
Eroziv osteoartrit: Tedaviye dirençli bir olgu sunumu
Keywords: Erosive osteoarthritis; inflammatory osteoarthritis; radiology; treatment